My treasury of Aesop's fables - Payne, Jan; Terry, Michael (Cottage Farm, Sywell, UK, Igloobooks, 2020, 2020)
Meet a jealous donkey, a tortoise who wants to fly, a very special goose and many other animals in this collection of tales, retold especially for children
English Stories
23
Keywords: Children's stories; Children's stories; Fables, Greek